2012
DOI: 10.1373/clinchem.2011.172676
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Plasma Glial Fibrillary Acidic Protein for Differentiating Intracerebral Hemorrhage and Cerebral Ischemia in Patients with Symptoms of Acute Stroke

Abstract: ,15 on behalf of the BE FAST Study Group BACKGROUND: Glial fibrillary acidic protein (GFAP) is a biomarker candidate indicative of intracerebral hemorrhage (ICH) in patients with symptoms of acute stroke. GFAP is released rapidly in the presence of expanding intracerebral bleeding, whereas a more gradual release occurs in ischemic stroke. In this study the diagnostic accuracy of plasma GFAP was determined in a prospective multicenter approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
133
2
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(150 citation statements)
references
References 40 publications
(49 reference statements)
6
133
2
1
Order By: Relevance
“…FNR represents the proportion of patients who would not have been sent to a CSC despite LAO, hence delaying optimal treatment, and FPR represents the proportion of patients who would have been sent to a CSC despite lack of LAO (futile transfers). The highest accuracy (79%; 95% confidence interval, 77-82) was observed for NIHSS score ≥11 (FNR, 27% [22][23][24][25][26][27][28][29][30][31][32]; FPR, 17% [14][15][16][17][18][19][20]), NIHSS score ≥14 (FNR, 39% [34][35][36][37][38][39][40][41][42][43][44]; FPR, 12% [9][10][11][12][13][14]), and RACE score ≥5 (FNR, 33% [28][29][30][31][32][33][34][35][36][37][38]; FPR, 15% [12][13][14]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…FNR represents the proportion of patients who would not have been sent to a CSC despite LAO, hence delaying optimal treatment, and FPR represents the proportion of patients who would have been sent to a CSC despite lack of LAO (futile transfers). The highest accuracy (79%; 95% confidence interval, 77-82) was observed for NIHSS score ≥11 (FNR, 27% [22][23][24][25][26][27][28][29][30][31][32]; FPR, 17% [14][15][16][17][18][19][20]), NIHSS score ≥14 (FNR, 39% [34][35][36][37][38][39][40][41][42][43][44]; FPR, 12% [9][10][11][12][13][14]), and RACE score ≥5 (FNR, 33% [28][29][30][31][32][33][34][35][36][37][38]; FPR, 15% [12][13][14]…”
Section: Resultsmentioning
confidence: 99%
“…Prehospital brain and arterial imaging using a mobile stroke unit might be an interesting option for patient triage in selected areas, but it remains to be demonstrated whether this expensive management approach is costeffective in the era of bridging therapy. [25][26][27] Other promising strategies that could help prehospital identification of stroke patients with LAO include serum biomarkers aiming to differentiate AIS and intracerebral hemorrhage 28,29 and automated or telemedicine-guided transcranial ultrasound imaging. 30,31 Our study has several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…Thus in the early hours after stroke, increased GFAP values could indicate intracerebral haemorrhage not ischaemia. Serum GFAP analysis performed within 4.5 hours of symptom onset can differentiate intracerebral haemorrhage and ischaemic stroke because GFAP levels are increased in patients with intracerebral haemorrhage compared with patients with ischaemic stroke [20]. GFAP has been reported to have high diagnostic accuracy for differentiating intracerebral haemorrhage from ischaemic stroke in patients within the acute phase of stroke symptom onset [21].…”
Section: Discussionmentioning
confidence: 99%
“…Out of these markers, glial fibrillary acidic protein (GFAP) is so far the most promising for translation into prehospital use. In several hospital cohorts in which samples were collected upon hospital arrival, GFAP has systematically demonstrated high sensitivity and specificity for diagnosing acute ICH [9][10][11]. For example, Foerch et al found sensitivity and specificity values of 84.2 and 96.3% respectively.…”
Section: Past Researchmentioning
confidence: 99%